"Far more poetry than justice." The economics of austerity in the America of Paul Auster. Issue 10 (5th September 2020) - Tedde, Adriano
Abstract: Moving beyond the modernist and postmodern metaphors of hunger that the writing of Paul Auster (b. 1947) suggests, this article explores Auster as a writer who responds to the so‐called public economic austerity that has dominated the political economic agenda in the United States during the past four decades. This reading suggests that there is a realist quality in Auster's work, notwithstanding its postmodern play. In presenting this argument, I believe that the writer's body of work discloses the history of post‐1960s American economy in a plethora of poverty‐stricken people that form the social background of his stories (downtrodden), in the insecurity that thwarts the main characters' existence (the newly dispossessed) and in the personal choices of the author himself to live his life as a starving artist (the penniless hero). Such an history of US economy is accompanied by a criticism of neoliberal ethos that restores the dignity of marginalized poor Americans.